AN ANALYSIS OF MATHEMATICAL LEARNING DIFFICULTIES BASED ON THE THEORY OF WANDINI AND ODA IN SOLVING FRACTION OPERATION PROBLEMS AMONG FIFTH-GRADE STUDENTS AT SD NEGERI MORKEPEK: AN ANALYSIS OF MATHEMATICAL LEARNING DIFFICULTIES BASED ON THE THEORY OF WANDINI AND ODA IN SOLVING FRACTION OPERATION PROBLEMS AMONG FIFTH-GRADE STUDENTS AT SD NEGERI MORKEPEK - Hendry, Dedy; Susanto, Dimas Kurniawan Budi Susanto; Ma’sum, Chandra Ali Ma’sum; Apriyanto, Indra Apriyanto; Rozi, Fahrur Rozi; Ellianawati, Ellianawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the difficulties in learning mathematics and the factors that cause difficulties in learning mathematics based on Wandini and Oda's theory in solving problems on fraction arithmetic operations in grade V students of Morkepek Elementary School. This study used a descriptive qualitative approach. This study used data collection techniques with interview and documentation studies. The results of this study are 1). Difficulties in learning mathematics in using facts, namely students have difficulty in translating fraction story problems into solutions according to symbols or fraction numbers correctly. 2). Difficulties in learning mathematics in using concepts, namely students are unable to master the prerequisite concepts of fraction arithmetic operations regarding determining the LCM. 3). Difficulties in using principles, namely students have difficulty in connecting fraction concepts into appropriate calculation relations. 4). Difficulties in using skills, namely students are unable to solve problems according to fraction calculation procedures.